AKUPRESUR TERHADAP PRODUKSI ASI PADA IBU POST PARTUM - Nur Djanah; Wafi Nur Muslihatun (Sistem Informasi, 2017)
Background: Breast feeding is one important pillars for babies because breast milk is the best nutrition for newborn up to 6 months old. Riskesdas data in 2013 showed that only 34.5% baby in Indonesia who are breastfeed exclusively, the meaning that there are stil about 2/3 of babies in Indonesia who less likely to get breast milk. The lack of production of breast milk is one of the obstacles in breast feeding exclusively. Acupressure is one of the non-pharmacologicalapproach, to improve the production of breast milk. Purpose: To describes the effect of acupressure to improve the production of breast milk with the indicators were baby weigh and the frequency of urinary. Methods: The design used was quasy experiment with pre and post test design. Total sample is 30. The sampling techniques with accidental sampling. Data was analyzed with Friedman test and followed by Willcoxon test. The independent variable waspostpartum mother and dependent variablle was the production of milk with the indicators were baby weight and the frequency of urinary. Instrument was using questionaire and observation sheet Results: The average birth weight was 3195 gram and the average of urinary was 6 times on the first day of newborn. Both indicators above was increased during the 2 and 4 weeks of born. The result of bivariat analysis showed there are the difference of weight with p value: 0,001 and the difference of frequency of urinary with p value: 0,001. Summary: That accupresure affects on breats milk production with the indicator of the baby wight and frequency of urinary.